Distribution characteristic and reserve formation of groundwater in the sandy coastal area of Quang Binh Province - Truong, Phan Van (Vietnam Journal of Earth Sciences, 2012)
The Quang Binh Province has the natural coastal sandy area of about 1,100km2, distributing in narrow strips that stretched along the coast. There are dense population and economic and cultural centers of Quang Binh province. The area is also prone to severe natural impacts and disadvantage in natural resources. Fresh underground water source is significant resource and plays an important role for socio-economic development of local areas. It is necessary to study comprehensively the formation and effective exploitation of groundwater in the study area.Distribution of groundwater in the Quaternary sediments in the sandy coastal area of Quang Binh coincides with geological formations of Holocene (qh) and Pleistocene aquifer (qp). The qh aquifer distributes mainly along estuary and adjacent sea areas under aluvial and aluvial-marine and ventifact-marine sediment (aQ23, amQ21-2, mvQ23).  The qp aquifer distributes in depressions on the ground under aluvial-marine (amQ1). The average depth of aquifers from 5 to 25m, in Quang Trach area is 13m, maximum is 48m, in Dong Hoi area is 9,71m. Especially, in the south of Quang Binh province, from Nhat Le river to Le Thuy, qh aquifer depth is from 20 to 30m.Groundwater is mainly originated from rain water with supply-permeability coefficient of 15-16%. Potential exploiting reserve of groundwater in Quang Binh is about 1,850,000m3/day, including static nature reserve: 68,000m3/day (5%) and dynamic nature reserve: 1,781,000m3/day (95%). Groundwater reserve is divided in two seasons, in which 77% formed in rainy season.